2016
DOI: 10.1007/s12094-016-1481-5
|View full text |Cite
|
Sign up to set email alerts
|

The number of risk factors is the strongest predictor of prostate cancer mortality: multi-institutional outcomes of an extreme-risk prostate cancer cohort

Abstract: Patients presenting at diagnosis with two extreme-risk criteria have almost fourfold higher risk for prostate cancer mortality. Such patients should be considered for more aggressive multimodal treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Tai et al ( 23 ) revealed that men with only one risk factor had a 5-year BCR-free survival rate of 76.9%, compared with 34.6% in men with ≥2 risk factors. Gomez-Iturriaga et al ( 24 ) identified 1,341 extreme-risk PCa (T3b–4, GS 9–10 or PSA >50 ng/mL; or patients with two or more high-risk factors: T2c–3a, GS 8 and PSA >20 ng/mL), and the 10-year BCR, clinical-free survival, PCSS and OS were 57.0%, 78.9%, 93.6%, and 71.3%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tai et al ( 23 ) revealed that men with only one risk factor had a 5-year BCR-free survival rate of 76.9%, compared with 34.6% in men with ≥2 risk factors. Gomez-Iturriaga et al ( 24 ) identified 1,341 extreme-risk PCa (T3b–4, GS 9–10 or PSA >50 ng/mL; or patients with two or more high-risk factors: T2c–3a, GS 8 and PSA >20 ng/mL), and the 10-year BCR, clinical-free survival, PCSS and OS were 57.0%, 78.9%, 93.6%, and 71.3%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Tai et al (23) revealed that men with only one risk factor had a 5-year BCR-free survival rate of 76.9%, compared with 34.6% in men with ≥2 risk factors. Gomez- Iturriaga et al (24) identified 1,341 extreme-risk PCa (T3b-4, GS 9-10 or PSA >50 ng/mL; or patients with two or more high-risk factors: T2c-3a, GS 8 and PSA >20 ng/mL), and the 10-year BCR, clinical-free survival, PCSS and OS were 57.0%, 78.9%, 93.6%, and 71.3%, respectively. The PCSS curve of seven groups showed that men with one risk factor of T3-4 had the best survival, and men with one risk factor of PSA >20 ng/mL had similar survival outcomes with those with two high-risk factors of T3-4 and PSA >20 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Iturriaga et al [23] identi ed 1341 extreme-risk PCa (T3b-4, GS 9-10 or PSA > 50 ng/ml; or patients with 2 or more high-risk factors: T2c-3a, GS 8 and PSA > 20 ng/ml), and the 10-year BCR, clinical-free survival, PCSS and OS were 57.0%, 78.9%, 93.6%, and 71.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although this trend was not significant and in contrast to previous controversial results, 4,8,9 if confirmed, it suggests that the CCP score may help stratify better highrisk localized prostate cancers into "favourable high-risk" and "unfavourable high-risk" groups, as it is been suggested from clinical factors in a previous study. 17 In addition to this, early failures (before 5 years) are more indicative of very aggressive disease and, therefore, clinically relevant due to higher possibility of these pts for disease specific mortality. 9,14 If true, then a high CCP score at diagnosis predicts micrometastatic disease, and these events would indicate the need for more aggressive treatment initially (i.e.…”
Section: Discussionmentioning
confidence: 99%